Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar IPS Siswa Kelas V - Prasetyawati, Rike; Sofarini, Andriana; Lokaria, Eka (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the completeness of the social studies learning outcomes of grade V students of SD Negeri Sadarkarya after implementing the Jigsaw-type cooperative learning model. The research method used is a pre-experimental design with a one-group pre-test and post-test design. The results of the study obtained an average final ability test score of 76.14. Data were analyzed using the Z-test with a significance level of 5% (0.05) obtained count (6.78) ≥ ztable (1.64). The conclusion is that with the implementation of the jigsaw-type cooperative learning model, the social studies learning outcomes of grade V students of SD Negeri Sadarkarya are significantly complete. Keywords: Jigsaw, Learning Outcomes, Social Studies